144k views
5 votes
Simplify (x^-1y^2)(-3x^2y^0)


Please help and explain

1 Answer

1 vote

We have
x^(-n) = \frac1{x^n} if
n is a positive integer and
x\\eq0, as well as
x^0 = 1 if
x\\eq0. So right away we can simplify to


\left(x^(-1) y^2\right) \left(-3 x^2 y^0\right) = \left(\frac{y^2}x\right) \left(-3x^2\right) = -\frac{3x^2y^2}x

If
x=0, then the starting expression is undefined. So we accept that
x=0, in which case
\frac xx = 1, and the overall expression simplifies to


\left(x^(-1) y^2\right) \left(-3 x^2 y^0\right) = \boxed{-3xy^2}

User Jolly Jumper
by
4.9k points